The quantum internet: A synergy of quantum information technologies and 6G networks - Georgi Gary Rozenman; Neel Kanth Kundu; Ruiqi Liu; Leyi Zhang; Alona Maslennikov; Yuval Reches; Heung Youl Youm (IET Quantum Communication, 2023)
Abstract The quantum internet is a cutting‐edge paradigm that uses the unique characteristics of quantum technology to radically alter communication networks. This new network type is expected to collaborate with 6G networks, creating a synergy that will fundamentally alter how we communicate, engage, and trade information. The improved security, increased speed, and increased network capacity of the quantum internet will lead to the emergence of a broad variety of new applications and services. The current state of quantum technology and its integration with 6G networks are summarised in this study, with an emphasis on the key challenges and untapped possibilities. The main goal is to get knowledge about how the quantum internet might impact communication in the future and alter several economic and societal sectors.